Comparative anatomy of calyx and foliar glands of Banisteriopsis C. B. Rob. (Malpighiaceae) - Araújo,Josiane Silva (2016)
Banisteriopsis is considered one of the largest genera of Malpighiaceae with 58 species, of which 47 occur in Brazil. The typical calyx and leaf glands of Banisteriopsis are considered relevant to the adaptive success of Malpighiaceae. Comparative studies of anatomical and histochemical characteristics may reveal similarities and assist in the interpretation of the functions performed by such glands. The present study aimed to describe the anatomy of the calyx and leaf glands of 38 species ofBanisteriopsis that occur in Brazil, and to analyze these structures histochemically in B. campestris, B. laevifolia and B malifolia, using standard methods. Calyx glands differ from leaf glands by possessing an irregular surface that is covered by a thick cuticle that is released from the epidermis by the accumulation of secretion; the glands are similar in all the other anatomical characteristics. Both types of glands produce secretions composed of a mixture of protein granules, lipids and polysaccharides. These findings reinforce the hypothesis that foliar glands have given rise to calyx glands in response to interactions with pollinators.